Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1038/s41598-021-91016-6
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-induced protein with tetratricopeptide repeats 3 may be a key factor in primary biliary cholangitis

Abstract: Accumulating studies suggest that senescent biliary epithelial cells (BECs) produce senescence-associated secretory phenotypes (SASPs) and play various roles in the pathogenesis of primary biliary cholangitis (PBC) and other cholangiopathies. We examined comprehensive profiles of senescent BECs and its contribution to the pathogenesis of PBC taking advantage of microarray analysis. cDNA microarray analysis revealed that 1841 genes including CCL2, IFIT3, CPQ were commonly up-regulated in senescent BECs cultured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 42 publications
(84 reference statements)
0
7
0
Order By: Relevance
“…Of relevance, CCL2 and fractalkine expression was increased in inflamed bile ducts in human PBC samples (Sasaki et al, 2010a). Moreover, senescent small ducts in PBC also express genes associated with inflammation and immune response (Sasaki et al, 2021). This work further highlights that biliary senescence induces a pro-inflammatory secretome within damaged cholangiocytes, which promotes inflammation and the recruitment of various inflammatory cells.…”
Section: Primary Biliary Cholangitismentioning
confidence: 53%
“…Of relevance, CCL2 and fractalkine expression was increased in inflamed bile ducts in human PBC samples (Sasaki et al, 2010a). Moreover, senescent small ducts in PBC also express genes associated with inflammation and immune response (Sasaki et al, 2021). This work further highlights that biliary senescence induces a pro-inflammatory secretome within damaged cholangiocytes, which promotes inflammation and the recruitment of various inflammatory cells.…”
Section: Primary Biliary Cholangitismentioning
confidence: 53%
“…36 The upregulation of IFIT3 suppressed apoptosis of biliary epithelial cells and may be associated with the pathogenesis of primary biliary cholangitis. 37 Moreover, IFIT3 also plays a vital role in the inflammatory processes of noninflammatory diseases. The knockdown of IFIT3 could significantly suppress the release of inflammatory cytokines in hepatic ischemia-reperfusion injury via the inhibition of STAT1 and STAT2 phosphorylation.…”
Section: Discussionmentioning
confidence: 99%
“…IFIT3 could stimulate the activation of cGAS/STING signaling pathway, which accounted for the pathogenesis of systemic lupus erythematosus 36 . The upregulation of IFIT3 suppressed apoptosis of biliary epithelial cells and may be associated with the pathogenesis of primary biliary cholangitis 37 . Moreover, IFIT3 also plays a vital role in the inflammatory processes of noninflammatory diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Sasaki and Nakanuma [31–33] previously reported that PBC patients exhibit increased senescent cholangiocytes; they also showed that, in vitro , the hydrophobic bile acid, GCDC promoted senescence likely via endoplasmic reticulum stress and dysregulated autophagy in cultured cholangiocytes [22]. More recently, Sasaki et al [34 ▪▪ ] performed a cDNA microarray analysis on cholangiocytes induced to senescence by serum depletion or persistent treatment with GCDC. The findings revealed increased expression of numerous chemokines and cytokines.…”
Section: Targetable Phenotypes Of Senescent Cholangiocytesmentioning
confidence: 99%